Analysis Of Lafadz Ta'liq Talak In Islamic Law Perspective And Civil Law Of Marriage/Compilation Of Islamic Law - -, Nurhadi (UI Scholars Hub, 2019)
Actually marriage is a sacred thing. The contract that unites the two opposite sexes is bound strongly (mitsaqan ghalizha). A strong agreement is concluded in the agreement between the guardian and the prospective husband. Indonesian civil law requires saying sighat ta’liq husband to his wife. The core content of sighat ta’liq is a conditional divorce between the two if the conditions have been fulfilled. Islamic law considers marriage to be legitimate if it has enough conditions and pillars, without sighat ta'liq. Indonesian law requires the requirements of sighat ta'liq in government policy through the decree of the minister of religion number 3 in 1953. The purpose of the existence of sighat ta’liq is to protect the wife from the abuse of her husband, if the husband violates the wife has the right to sue the religious court (divorce). Lafadz sighat ta’liq was made referring to the regulation of the minister of religion number 2 in 1990, but the lafadz contained a new understanding of marriage and the promise of divorce. Compilation of Islamic Law (KHI) as an explanatory regulation from UUP number 1 of 1974 Article 46 paragraph 3 does not require sighat ta’liq.